Solution:
Given the function f(x) and g(x) expressed as
![\begin{gathered} f(x)=√(x) \\ g(x)=x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9dyupucywc9hae0zof75m1cca4nm1vm8me.png)
C)
![(f\circ g)(7)](https://img.qammunity.org/2023/formulas/mathematics/college/qf2fdcv2nognd9m0rxt8gwn58jx2c0jjjf.png)
To evaluate,
step 1: Determine the function (f o g)(x).
The (f o g)(x) can be expressed as
![f(g(x))](https://img.qammunity.org/2023/formulas/mathematics/high-school/lxt6m05mtw4ipettwio31eom9wwt8qtext.png)
This implies that the g(x) function is substituted into the f(x) function.
Thus,
![\begin{gathered} (f\circ g)(x)=f(g(x))=f(x-3) \\ \Rightarrow(f\circ g)(x)=√((x-3)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fa6iokmq1g5miwfv7qeadyavl20jpsvbnf.png)
step 2: Evaluate (f o g)(7).
This is evaluated by substituting the value of 7 for x into the (f o g)(x) function.
Thus,
![\begin{gathered} \begin{equation*} (f\circ g)(x)=√((x-3)) \end{equation*} \\ \Rightarrow(f\circ g)(7)=√((7-3)) \\ =√(4) \\ \Rightarrow(f\circ g)(7)=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3fi4l1hx2v2qv9a8mj9omrxh6n2o12tcwz.png)
Hence, the value of the function (f o g)(7) is 2.
D)
![(g\circ f)(7)](https://img.qammunity.org/2023/formulas/mathematics/college/bfhi0s1149ewy4jttefir5tca4wr355lpn.png)
To evaluate,
step 1: Determine the function (g o f)(x).
The function (g o f)(x) can be expressed as
![g(f(x))](https://img.qammunity.org/2023/formulas/mathematics/college/3czgrg3kpv398n4rhr22wnihb1kc0wpkim.png)
This implies that the f(x) function is substituted into the g(x) function.
Thus,
![\begin{gathered} (g\circ f)(x)=g(f(x))=g(√(x)) \\ \Rightarrow(g\circ f)(x)=√(x)\text{ -3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8m7maq5ez7td13519du6dtf4nnps8x0k10.png)
step 2: Evaluate (g o f)(7).
This is evaluated by substituting the value of 7 for x into the (g o f)(x) function.
Thus,
![\begin{gathered} \begin{equation*} (g\circ f)(x)=√(x)\text{ -3} \end{equation*} \\ \Rightarrow(g\circ f)(7)=√(7)\text{ -3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dxgk1ahopwjcj40sxnst71edtmbpkg0kot.png)
Hence, the value of the function (g o f)(7) is (√7 - 3).